Considerations in Adolescent Use of the Etonogestrel Subdermal Implant: A Cohort Study - Fei, Y. Frances; Smith, Yolanda R.; Dendrinos, Melina L.; Rosen, Monica W.; Quint, Elisabeth H. (Frontiers in Reproductive Health, 2021)
Objectives To describe bleeding patterns and other side effects in adolescent implant users and characterize their impact on early discontinuation of the implant. Study Design This is a retrospective cohort study of female patients under 18 years who had an implant placed from 2013-2018. Data were collected on demographics, medical history, and side effects. Results Of 212 adolescents, the average age at insertion was 16 years and 84% desired placement for contraception. Common side effects included AUB (80%), mood changes (10%), and perceived weight gain (9%). Most (76%) used the implant for at least 12 months. Average time to removal was 22.1 months (SD 13.0 months) and this did not depend on presence of side effects. Twenty-seven percent of teens were able to achieve amenorrhea. Adolescents with frequent or prolonged bleeding were more likely to have implant removal prior to 12 months than those with other bleeding patterns (p=0.003). Early removal was also more common in girls reporting weight or mood issues than those who did not (p<0.001 and p=0.045, respectively). BMI increased in 64% of adolescents. Average percentage change in BMI was 3.2% (0.87 kg/m2). There was no difference in baseline use of any mood-modulating medications in patients who did and did not complain of mood side effects following implant placement (p=0.801). Conclusion Characterization of bleeding patterns following implant placement in adolescents have not previously been reported. Prolonged or heavy bleeding, mood issues, and perceived weight gain were associated with earlier removal of the implant. A relatively small number had early removal of the implant due to weight or mood complaints. Therefore, a history of obesity, depression, or other mood disorders should not be a deterrent to implant placement.